Trends in usage and regional variations in Ethiopian animal feeding practices: A 15-year analysis for informed policy - Desalegn Begna; Zemene Yohannes; Netsanet Jote; Girma Teshome; Alemnew Mekonen (PLoS ONE, 2026)
Livestock feeding practices play a pivotal role in sustaining agricultural productivity and food security in Ethiopia. However, the sector continues to face structural challenges, including a heavy reliance on traditional feed resources and pronounced regional disparities. This study utilized secondary data from the Agricultural Sample Surveys conducted annually by the Central Statistical Agency (2004/05–2018/19) to assess feeding practices, examine regional variations, and analyze long-term trends. Descriptive statistics, trend analysis, and correspondence analysis were applied. Different data analytical techniques were employed, including descriptive statistics, trend analysis, and Correspondence Analysis (CA), were employed to monitor livestock feeding practices, examine the regional differences, and explore trends over the long horizon. Results showed a decline in reliance on green fodder (from 40.3% to 36.9%) and crop residues (from 33.5% to 32.0%), accompanied by a modest increase in the use of improved feeds (0.15% to 0.90%) and agro-industrial by-products (2.7% to 4.6%). Regional differences were substantial: Afar predominantly used green fodder (82%), while Harari relied more on crop residues (41%). In high-livestock-population regions such as Amhara, Oromia, and SNNP, feeding practices varied according to resource availability and management strategies. These findings underscore the need for targeted, region-specific interventions to enhance feed availability, promote adoption of sustainable and cost-effective feeding systems, and address persistent demand–supply imbalances. The evidence also offers insights for policy reforms in other agriculture-based developing economies.